In vitro Validation of Chimeric β-Galactosylceramidase Enzymes With Improved Enzymatic Activity and Increased Secretion - Ricca, Alessandra; Cascino, Federica; Morena, Francesco; Martino, Sabata; Gritti, Angela (Frontiers in Molecular Biosciences, 2020)
Globoid Cell Leukodystrophy (GLD) is a lysosomal storage disease (LSD) caused by inherited defects of the β-galactosylceramidase (GALC) gene. The infantile forms display a rapid and aggressive central and peripheral nervous system (CNS and PNS) dysfunction. No treatments are available for GLD patients. Effective gene therapy (GT) strategies for GLD require a safe and widespread delivery of the functional GALC enzyme to all affected tissues/organs, and particularly to the CNS. The use of chimeric lysosomal enzymes with increased secretion and enhanced transport across the blood-brain barrier (BBB) that boost the efficacy of GT approaches in pre-clinical models of similar neurodegenerative LSDs may benefit GLD as well. Here, we tested the safety and biological efficacy of chimeric GALC enzymes engineered to express an alternative signal peptide (iduronate-2-sulfatase - IDSsp) and the low-density lipoprotein receptor (LDLr)-binding domain from the Apolipoprotein E II (ApoE II) in GLD murine neural and hematopoietic stem/progenitor cells and progeny, which are relevant cells types in the context of in vivo and ex vivo GT platforms. We show that the lentiviral vector-mediated expression of the chimeric GALC enzymes is safe and leads to supranormal enzymatic activity in both neural and hematopoietic cells. The IDSsp.GALC shows enhanced expression and secretion in comparison to the unmodified GALC. The chimeric GALC enzymes produced by LV-transduced cells reduce intracellular galactosylceramide (GalCer) storage and effectively cross-correct GLD murine neurons and glial cells, indicating that the transgenic enzymes are delivered to lysosomes, efficiently secreted, and functional. Of note, the expression of LDLr and LDLr-related proteins in GLD neurons and glial cells supports the exploitation of this system to enhance the GALC supply in affected CNS cells and tissues. These in vitro studies support the use of chimeric GALC enzymes to develop novel and more effective GT approaches for GLD.